Kondisi Psikologis Atlet Olahraga Karate Menjelang Pertandingan - Pangistu, Theo (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to identify the psychological factors that play a role in the performance of karate athletes, assist coaches and decision-makers in developing more effective training programs, and understand how athletes manage their psychological conditions. This research employs a qualitative approach using a case study method. Data is collected through in-depth interviews with karate athletes, coaches, and sports psychologists. Observations are also conducted during training sessions and competitions to obtain a more comprehensive understanding of the athletes' psychological conditions. The results of this research showed that most athletes admitted to experiencing anxiety before the match. Some athletes also experience somatic anxiety such as heart palpitations, sweating and muscle tension and some athletes express that they feel depressed because they are afraid of disappointing the people around them if they cannot give their best performance. In conclusion, these results can contribute to the development of mental and psychological training programs specific to the sport of karate. Keywords: psychological condition, karate athletes, anxiety, stress, self-confidence, performance, competition.